Hubungan Dinamika Kelompok Dengan Kinerja Bumdes: Studi Kasus BUMDes Mandiri Bersatu Pekon Gisting Bawah: The Relationship of Group Dynamics and Bumdes Performance: Case Study of Bersatu Mandiri BUMDes Gisting Bawah Village - Niat Pamungkas; Yuniar A Syarief; Helvi Yanfika (Journal of Agriculture and Social Development, 2023)
Group dynamics is a method that aims to increase the value of group cooperation. BUMDes performance is the result or work performance and how the work process takes place. This study aims to determine the dynamics of the group at BUMDes Mandiri Bersatu and the relationship between group dynamics on the performance of BUMDes Mandiri Bersatu in Pekon Gisting Bawah, Gisting District, Tanggamus Regency. This study used the census method. The research location was chosen deliberately with the consideration of having the largest equity participation of 450,000,000 or 43.9% of the total equity participation of BUMDes in Gisting District. The research was conducted in November 2022. The group dynamics that occurred in Mandiri Bersatu BUMDes were analyzed using quantitative descriptive analysis and the relationship of group dynamics to BUMDes performance was analyzed using non-parametric statistics with the Rank Spearman correlation test. The results showed that of the nine elements of group dynamics in the Mandiri Bersatu BUMDes, only group structure and hidden intentions had a moderate category, while the other seven variables had a high category. Group dynamics variables that have a close relationship with the performance of the Mandiri Bersatu BUMDes are group goals, group cohesiveness, and group effectiveness.